2007
DOI: 10.1017/s0033822200042685
|View full text |Cite
|
Sign up to set email alerts
|

Two Decades of Regular Observations of 14CO2 and 13CO2 Content in Atmospheric Carbon Dioxide in Central Europe: Long-Term Changes of Regional Anthropogenic Fossil CO2 Emissions

Abstract: Time series are presented of radiocarbon and 13C contents in atmospheric carbon dioxide over eastern Europe (southern Poland), covering the periods 1983–1994 and 2000–2004. The carbon isotope composition was measured in biweekly composite samples of atmospheric CO2, collected about 20 m above the local ground level. The data for 2 observational sites are presented: i) city of Kraków (50°04′N, 19°55′E; 220 m asl; for 1983–1994 and 2000–2004); and ii) Kasprowy Wierch, Tatra Mountains (49°14′N, 19°56′E; 1989 m as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…years 1900-2002. A distinct offset of  14 CO 2 values observed at Kraków station with respect to the European reference background curve is attributed to local emissions of CO 2 originating mostly from burning of fossil fuels within the Kraków agglomeration (Kuc et al 2007). During the 1980s, the average offset was equal to 55‰ for the annual averages and ~30‰ for the growing-season means.…”
Section: Climatic Datamentioning
confidence: 84%
“…years 1900-2002. A distinct offset of  14 CO 2 values observed at Kraków station with respect to the European reference background curve is attributed to local emissions of CO 2 originating mostly from burning of fossil fuels within the Kraków agglomeration (Kuc et al 2007). During the 1980s, the average offset was equal to 55‰ for the annual averages and ~30‰ for the growing-season means.…”
Section: Climatic Datamentioning
confidence: 84%
“…Anthropogenic and biogenic contributions of CO 2 to an urban atmosphere were studied using several approaches, mostly involving carbon and oxygen isotopes in CO 2 [7][8][9][10][11][12]. Levin et al [8] used analyses of the 14 CO 2 content in atmospheric CO 2 samples collected weekly in a densely populated area of the Rhine valley in Germany to determine the contribution of fossil fuel-derived CO 2 to the local urban atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Using isotope mass balance approaches, they were able to demonstrate that, apart from anthropogenic CO 2 , also a significant contribution originating from local biogenic sources is present in the investigated urban atmosphere. Kuc et al [9] used a similar approach using biweekly cumulative sampling of atmospheric CO 2 in the urban atmosphere of Krakow. They found that both concentration and isotopic composition ( 14 C/ 12 C and 13 C/ 12 C) of atmospheric CO 2 in the urban environment differ distinctly from atmospheric baseline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This is strictly true in the limit that the time (and space) between background and observation goes to zero. Some authors [e.g., Riley et al, 2008;Kuc et al, 2007] have instead assumed that D 14 C of photosynthesis is equal to D obs , and in this case, equation (3) can be rewritten as…”
Section: Introductionmentioning
confidence: 99%